School Administrators’ Leadership Competencies and Teachers’ Resilience During Covid-19 Pandemic - Hostallero, Michael Ballon; Cabal, Esmen M. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
This study investigated the relationship between school adminis-trators’ leadership competencies and teachers’ resilience during the COVID-19 pandemic in the Zone 1 Division of Zambales for the school year 2020-2021. Using a descriptive research design, data were gathered from 136 randomly selected principals and teachers through a questionnaire. Results indicated that the school admin-istrators were rated "Excellent" in the leadership dimensions of managing change, solving problems, taking risks, setting vision, and demonstrating ethics and integrity. Similarly, teachers were assessed as "Excellent" in the resilience dimensions of self-awareness, realism, keeping calm under stress, empathy, and self-control. No significant difference was found in the perceptions of the school administrators and teachers regarding the administra-tors’ leadership competencies. However, a significant difference was observed in the perceptions of teachers' resilience. The study further revealed a positive high correlation between administra-tors’ leadership competencies and teachers’ resilience. Based on these findings, it was recommended that school heads continue to employ democratic principles, embrace new ideas, and adapt to change while maintaining ethical integrity. Moreover, strengthen-ing the partnership between school administrators and teachers is essential in achieving the school’s vision and objectives. Future researchers are encouraged to conduct parallel studies to validate these results and support the development of effective leadership practices.